Sistem Informasi Distribusi Rekam Medis ( Studi Kasus : RSAU Lanud Sulaiman ) - Syifa Ansori; Irda Sari; Candra Sufyana (Jurnal Sains dan Informatika, 2022)
Sulaiman Air Force Base Hospital is a hospital that organizes service activities for members of the Indonesian Air Force and family members, as well as serving the general public, especially in terms of health. The medical record distribution information system is needed to support services to patients and assist the process of searching and monitoring medical records out and back from the patient's destination polyclinic. The distribution of medical records at the Sulaiman Air Base Hospital has not been computerized in terms of recording and reporting. Thus, the purpose of this research is to design a medical record distribution information system that facilitates the process of recording reports and searching for medical records as well as monitoring the distribution of medical records. The research method using a qualitative descriptive approach, as well as data collection based on field observation techniques, also uses library research techniques by analyzing several references. The system development method uses the waterfall, as well as the stages of system design with Data Flow Diagrams programming language VB.NET . It is hoped that the medical record distribution information system designed in this study can help the medical record distribution process so that it can run well and efficiently. Keywords: DFD, Distribution, Medical Records, Information System